TINJAUAN KESATUAN DARI KEPELBAGAIAN MENURUT KITAB-KITAB INJIL DAN SURAT-SURAT PAULUS - Waharman Waharman (Manna Rafflesia, 2018)
The purpose of this writing is so that church officials and all church members truly realize that they are members of the body of Christ. Just as the limbs seem less important but are given special respect, they are not needed by beautiful members. Based on the analogy of the church as the body of Christ, the church division is something that is very absurd, something that does not make sense to happen. Where there are limbs that conflict with one another. It is very insane for members to hurt one another. But historical reality has not counted how many conflicts have caused disunity. Believers have failed to analogize themselves with the Body of Christ. The Church is not an earthly organization or social institution. The church is the body of Christ and should not be treated as a social organization. The church is beyond any organization because there is life in it. A deep awareness of the church as the body of Christ will lead to responsibility, humility to cooperate, avoiding the danger of division which often threatens the integrity of the church.